THE MODEL OF EXTERNSHIP ORGANIZATION FOR FUTURE TEACHERS: QUALIMETRIC APPROACH - Taisiya A. Isaeva (Obrazovanie i Nauka)
The aim of the paper is to present author’s model for bachelors – future teachers of vocational training. The model is been worked out from the standpoint of qualimetric approach and provides a pedagogical training.Methods. The process is based on the literature analysis of externship organization for students in higher education and includes the SWOT-analysis techniques in pedagogical training. The method of group expert evaluation is the main method of pedagogical qualimetry. Structural components of professional pedagogical competency of students-future teachers are defined. It allows us to determine a development level and criterion of estimation on mastering programme «Vocational training (branch-wise)».Results. This article interprets the concept «pedagogical training»; its basic organization principles during students’ practice are stated. The methods of expert group formation are presented: self-assessment and personal data.Scientific novelty. The externship organization model for future teachers is developed. This model is based on pedagogical training, using qualimetric approach and the SWOT-analysis techniques. Proposed criterion-assessment procedures are managed to determine the developing levels of professional and pedagogical competency.Practical significance. The model is introduced into pedagogical training of educational process of Kalashnikov’s Izhevsk State Technical University, and can be used in other similar educational establishments.